Analisis Psikologis Kesiapan Masyarakat Osing Banyuwangi dalam Menggunakan QR Payment - Hariyadi, Atim; Padilah, Raup (Universitas Palangka Raya, 2024)
The development of digital payment technology has experienced rapid growth in Indonesia, one of which is the use of QR payment. This article aims to analyze the psychological readiness of the Osing community in Banyuwangi in adopting QR payment technology. Through a descriptive quantitative research approach, this study measures psychological factors influencing the acceptance of new technology, such as self-efficacy, perceived ease of use, and attitudes towards technological innovation. This research employed a descriptive quantitative method with a sample of 150 respondents from the Osing community, selected using a stratified random sampling technique. The results of the study show that attitudes toward technology and perceived ease of use received the highest scores, 4.2 and 4.0 respectively, on a Likert scale. However, low perceptions of security (3.5) and self-efficacy (3.8) indicate barriers to the community’s readiness. Additionally, traditional social norms, with a score of 3.6, also affect the adoption rate of technology within the Osing community. Therefore, despite the positive potential for the acceptance of QR payment technology, further education and community-based approaches are needed to improve trust and skills in using the technology.